Range-wide population genetic structure of the European bitterling (Rhodeus amarus) based on microsatellite and mitochondrial DNA analysis - Bryja, J; Smith, C; Konečný, A; Reichard, M (Molecular ecology, 2010)
An understanding of recent evolutionary processes is essential for the successful conservation and management of contemporary populations, especially where they concern the introduction or invasion of species outside their natural range. However, the potentially negative implications of intraspecific introductions and invasions have attracted less attention, although they also represent a potential threat to biodiversity, and are commonly facilitated through human activities. The European bitterling (Rhodeus amarus) is a small cyprinid fish that decreased greatly in its distribution during the 1970s and 1980s and was subsequently included on many European conservation lists. This decline appears to have reversed, and the extent of its distribution now exceeds its former range. We used a combination of 12 microsatellite markers and cytochrome b sequences on a large data set (693 individuals) across the current range of the European bitterling to investigate possible scenarios for its colonization of Europe. We show that the inferred history of colonization of Europe was largely congruent between mitochondrial and nuclear markers. The most divergent mtDNA lineages occur in the Aegean region but probably are not reproductively isolated as the Aegean populations also displayed mtDNA haplotypes from other lineages and nuclear data indicated their close relationship to Danubian populations. Much of Europe is currently populated by descendants of two main lineages that came to natural secondary contact in western Europe. An approximate Bayesian computation analysis indicates different dates for admixture events among western and central European populations ranging from the last deglaciation (natural) to the last few centuries (human-assisted translocations).
Keywords: Microsatellite Repeats; molekulární evoluce; Europe; mitochondriální DNA; Genetics, Population; Genotype; Geography; Genetic Variation; Evropa; Bayesova věta; populační genetika; Animals; DNA, Mitochondrial; modely genetické; Sequence Analysis, DNA; zvířata; genetická variace; fylogeografie; Bayes Theorem; Phylogeography; mikrosatelitní repetice; Models, Genetic; Cyprinidae; sekvenční analýza DNA; genotyp; Evolution, Molecular; zeměpis